Endurance in long-distance swimming and the use of nutritional aids - Miguel-Ortega, Á.; Calleja-González, J.; Mielgo-Ayuso, J. (Nutrients, 2024)
Background: Long-distance swimmers exert energetic, physiological, and neuromuscular demands that must be matched with adequate body composition to improve their performance in long-distance swimming.